Karakteristik dan Motivasi Wisatawan Mancanegara yang Berkunjung ke Pantai Batu Bolong, Canggu, Kabupaten Badung, Bali - Devi, Tiara; Sukana, Made (JURNAL DESTINASI PARIWISATA, 2024)
Canggu has a reputation and beach image that has grown rapidly in recent years. This tourist attraction has attracted foreign tourists with various characteristics and motivations to visit Batu Bolong Beach, Canggu. This research aims to collect information about foreign tourists who visit Batu Bolong Beach, especially regarding age, gender, education, income level and length of visit. Apart from that, it aims to identify and analyze the main motivations of foreign tourists for visiting Canggu Beach. The research methodology used is Mix Method, namely qualitative and quantitative. This research used 50 foreign tourist respondents. The results of this research are dominated by tourists from France, male, aged 21-30, not married, frequency of visits to Bali 3-4 times, frequency of visits to Batu Bolong Beach 2-3 times, length of visit 1- 2 hours, visit with friends, and the purpose of the visit is for recreation. Meanwhile, the motivation for tourists to visit Batu Bolong beach is to relieve fatigue from the work environment, relax, swim, surf, sunbathe, romance with their partner, strengthen family relationships, education, visit new places, a dream, interaction with local people, to see beautiful beach, easy to reach location, affordable entrance ticket, and beach facilities. Keywords: Characteristics, Motivation, Batu Bolong Beach